Exploring enzymatic antioxidant activities in Asian Elephant (Elephas maximus) sperm and seminal plasma - Yuqing Yang; Junpen Suwimonteerabutr; Taweepoke Angkawanish; Nicole Sirisopit Mehl; Patharapol Piamsomboon; Nuttawadee Ngamlertwong; Padet Tummaruk; Pakpoom Navanukraw; Phakjira Sanguansook; Kaywalee Chatdarong (Theriogenology Wild)
This study explored the relationships between sperm quality and the activities of antioxidant enzymes (superoxide dismutase, SOD, and glutathione peroxidase, GPx) in sperm (S) and seminal plasma (SP) of Asian elephants, as well as the potential protective role of glutamine in semen extenders during chilled storage. In experiment 1, twenty ejaculates from 11 bulls were analyzed for percentages (%) of sperm motility (%MOT), viability (%VIA), and activities of SOD and GPx. A significant negative correlation was found between %VIA and SP-SOD (r = − 0.71), and positive correlations between %MOT and both S-GPx (r = 0.49) and SP-GPx (r = 0.57). Following these findings, glutamine, a precursor of glutathione and semen antioxidant was introduced in Experiment 2. Each ejaculate (in a total of 8 ejaculates obtained from four bulls) was diluted in Tris-fructose- (EYT) and Tris-glucose-egg yolk extender (TCG), respectively, supplemented with 0 (control), 20 and 40 mM glutamine and stored at 4 °C. Sperm parameters including %MOT, %VIA, functional membrane integrity (%sHOST), and DNA integrity (%DNA) were assessed after 24 and 48 h of storage. Results demonstrated that glutamine did not significantly affect %VIA or %DNA. A significant reduction in %MOT was observed at 24 h, but 20 mM glutamine added in extenders reversed this decline at 48 h. A 40 mM addition of glutamine in TCG markedly reduced %sHOST at 24 h. In conclusion, SOD and GPx activities in the sperm and seminal plasma are indicative of sperm quality. During chilling, using a higher level of glutamine may damage the spermatozoa of Asian elephants.